Effect Of Sarpaghandaghan Vati and Arjunarishta In Raktaghatvata w.s.r To Hypertension: A Case Study - bhardwaj, Khushboo (International Research Journal of Ayurveda & Yoga, 2021)
Hypertension is a common disease in present era. Every fifth person is found hypertensive. Most adults develop it, in later half of their life more than 50% of the deaths and disabilities from heart disease and stroke together kill more than 12 million people each year. It has been predicted that by the year 2020 there will be a 75% increase in the global cardiovascular disease burden occurring. Hypertension results from a variety of reasons like stress, obesity, genetic, factors, over use of salts in the diet and ageing. As we all know, hypertension is a silent killer because it rarely exhibits symptoms before it damages the heart, brain, or kidney. At present era there are many anti-hypertensive drugs are available in modern medicine, but none of them is free from untoward effects. Ayurveda can be described as a real science of life. Ayurveda concentrates on achieving the promotion of health, prevention and management of disease for a healthy and happy life in the ailing society. The principles of Ayurveda are focused on maintaining good health by good diet and good lifestyle. In Ayurveda texts books there is no clear pronunciation of Hypertension; According to Acharya Charak, sometimes neither it is possible nor it’s necessary to identify a disease by a name (Anuktavyadhi). An Ayurvedic physician should attempt to understand Samprapti (pathogenesis) of a given clinical conditions on the basis of signs, symptoms, acuteness, chronicity, complication with investigative findings in each case and should plan the management accordingly.